Relation of Temperature and Humidity to the Risk of Recurrent Gout Attacks - Neogi, T.; Chen, C.; Niu, J.; Chaisson, C.; Hunter, D. J.; Choi, H.; Zhang, Y. (American journal of epidemiology, 2014)
Gout attack risk may be affected by weather (e.g., because of volume depletion). We therefore examined the association of temperature and humidity with the risk of recurrent gout attacks by conducting an internet-based case-crossover study in the United States (in 2003-2010) among subjects with a diagnosis of gout who had 1 or more attacks during 1 year of follow-up. We examined the association of temperature and humidity over the prior 48 hours with the risk of gout attacks using a time-stratified approach and conditional logistic regression. Among 632 subjects with gout, there was a significant dose-response relationship between mean temperature in the prior 48 hours and the risk of subsequent gout attack (P = 0.01 for linear trend). Higher temperatures were associated with approximately 40% higher risk of gout attack compared with moderate temperatures. There was a reverse J-shaped relationship between mean relative humidity and the risk of gout attacks (P = 0.03 for quadratic trend). The combination of high temperature and low humidity had the greatest association (odds ratio = 2.04, 95% confidence interval: 1.26, 3.30) compared with moderate temperature and relative humidity. Thus, high ambient temperature and possibly extremes of humidity were associated with an increased risk of gout attack, despite the likelihood that individuals are often in climate-controlled indoor environments.